How Effective is Cognitive Remediation in Enhancing Vocational Outcomes for Job Seekers with Severe Mental Illness in Australia?. (2nd December 2016) - Contreras, Natalia A.; Castle, David J.; Crosse, Caroline; Morgain, Dea; Fossey, Ellie; Harvey, Carol; Rossell, Susan L.
Abstract : Objective: Despite advances in the treatment of people with severe mental illness (SMI), access to work for this community still remains a challenge. Cognitive remediation (CR) is an intervention that can improve employment outcomes, especially when offered alongside employment support. This pilot study aimed to determine whether CR enhances vocational outcomes for job seekers participating in an innovative vocationally oriented psycho‐educational program implemented in Australia. Method: Fourteen participants with SMI were enrolled in Health Optimisation Program for Employment (HOPE) and attended 20 sessions of CR. Assessments were performed at baseline, post‐CR, and 3 months follow‐up. Individuals were assessed on a number of occupational and psychosocial variables (e.g., hours of paid and unpaid work, self‐esteem, quality of life, social relationships), in addition to undertaking the MATRICS Consensus Cognitive Battery. Results: There was no increase in hours of paid work for those in employment, but 46% of the group initiated tertiary studies between baseline and 3‐month follow‐up. There was a trend towards a significant increase in number of volunteer hours, with 31% of individuals having initiated a non‐paid activity at the end of the CR. As predicted, cognition improved over time as did psychosocial outcomes in the areas of self‐esteem, quality of life and social relationships. Conclusions: Consistent with previous studies, CR improved psychosocial and cognitive functioning. While employment benefits were not found, promising outcomes were reported on volunteering and educational participation. This pilot suggests there may be potential for combining CR with HOPE to enhance vocation‐related participation and potential employability of job seekers with SMI in Australia. Given these preliminary findings, a further clinical trial with appropriate control group and sample size is required to validate the effectiveness of HOPE+CR.